دور البرامج الحوارية الفضائية في تدعيم المشاركة في الأنشطة الاجتماعية لدى عينة من طلبة جامعة دمشق (دراسة ميدانية في كليات الاقتصاد- التربية – الطب بجامعة دمشق) - الشماس عيسى; يونس لينا (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدف البحث إلى تعرف دور البرامج الحوارية الفضائية في تدعيم المشاركة في الأنشطة الاجتماعية لدى عينة من طلبة جامعة دمشق. وتعرف دلالة الفروق في إجابات أفراد عينة البحث على استبانة دور البرامج الحوارية واستبانة الأنشطة الاجتماعية وفق متغيرات البحث: (الجنس، نوع التخصص الجامعي، السنة الدراسية). واعتمدت الباحثة على المنهج التحليلي الوصفي، واستخدمت أداة البحث: (مقياس الأنشطة الاجتماعية). وشملت عينة البحث (484) طالباً وطالبةً في كليات الاقتصاد والتربية والطب في جامعة دمشق. ومن أهم النتائج التي توصل إليها البحث: 1) إنَّ دور البرامج الحوارية في تدعيم المشاركة في الأنشطة الاجتماعية لدى عينة من طلبة جامعة دمشق كان بدرجة متوسطة بلغ وزنها النسبي (65.87%). 2) عدم وجود فروق ذات دلالة إحصائية بين متوسطات إجابات أفراد عينة البحث على استبانة الأنشطة الاجتماعية وفق متغير الجنس. 3) عدم وجود فروق ذات دلالة إحصائية بين متوسطات إجابات أفراد عينة البحث على استبانة الأنشطة الاجتماعية وفق متغير نوع التخصص الجامعي. 4) وجود فروق ذات دلالة إحصائية بين متوسطات إجابات أفراد عينة البحث على استبانة الأنشطة الاجتماعية وفق متغير السنة الدراسية لصالح طلبة السنة الرابعة. The research defines the role of TV talk shows in strengthening participation in social activities in a sample of students at the University of Damascus and know denoting differences in the answers of the research sample to identify the role of talk shows and the identification of individuals and social activities according to research variables (gender, type of university specialization, and school year). The researcher adopted an analytical descriptive approach and used the research tool: (a measure of social activities). The research sample included 484 male and female students in the faculties of economics, education and medicine at the University of Damascus. Among the most important findings of the research: 1) The role of talk shows in strengthening the participation in social activities among a sample of Damascus University students moderately reached the relative weight (65.87%). 2) The lack of statistical significance between the mean differences in answers to members of the research sample to identify social activities in accordance with the variable of sex. 3) The lack of statistical significance between the mean differences in answers to members of the research sample to identify social activities in accordance with the type of a variable of university specialization. 4) No statistically significant differences between the mean of the answers of the research sample to identify members of the social activities of the school year in accordance with the variable of the fourth year students.